2009
DOI: 10.1097/fch.0b013e3181b91f72
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Action Research With 2 Vulnerable Populations

Abstract: Eliminating health disparities involving minority groups is a major national priority. Action research, a response to this national priority, may be derived from different theoretical models. The purposes of action research are to involve key community stakeholders in developing knowledge and taking pragmatic action to solve problems. In this article, the authors examine how the model was put into action for 2 distinct programs of research, comparing and contrasting final results, one report primarily focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The relatively high refusal rate of 9 of the 13 (69%) referrals may reflect the importance of personal relationships in the Mexican culture. 4,21,27 These potential participants received a telephone call from study personnel but had no personal relationship with the caller. Face-to-face contact, personal relationships, and grant staff from the target community are important recruitment strategies in the Mexican American population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively high refusal rate of 9 of the 13 (69%) referrals may reflect the importance of personal relationships in the Mexican culture. 4,21,27 These potential participants received a telephone call from study personnel but had no personal relationship with the caller. Face-to-face contact, personal relationships, and grant staff from the target community are important recruitment strategies in the Mexican American population.…”
Section: Resultsmentioning
confidence: 99%
“…Face-to-face contact, personal relationships, and grant staff from the target community are important recruitment strategies in the Mexican American population. 4,13,21,25,27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies with Hispanic individuals also reported that the purpose of the study (to improve the health of the MA community) was rated as even more important than other aspects (Kneipp, Lutz, & Means, 2009; Larson et al, 2009). Also, the necessity to reiterate that the study did not provide direct services occurred in previous studies (Crist, Parsons et al, 2009). …”
Section: Other Issuesmentioning
confidence: 98%
“…We viewed in-patients, their families, and staff at the hospital as the community with which to collaborate (Crist, Parsons et al, 2009). …”
Section: Other Issuesmentioning
confidence: 99%